Strengthening Polymer Concrete with Carbon and Basalt Fibres; Applied Sciences; Vol. 14, iss. 17 - Ikbaeva A. Akzharkyn; Elemesov K. K. Kasym Koptleuevich; Baskanbaeva D. D. Dinara Dzhumabaevna; Martyushev N. V. Nikita Vladimirovich; Skeeba V. Yu. Vadim Yurjevich; Konyukhov V. Yu. Vladimir Yurjevich; Oparina T. A. Tatjyana Anatoljevna (2024, 2024)
Title screen